Excimer laser atherectomy to overcome intraprocedural obstacles in chronic total occlusion percutaneous intervention: Case examples. Issue 3 (7th October 2014) - Sapontis, James; Grantham, J. Aaron; Marso, Steven P.
<x xml:space="preserve">Abstract</x> Technical advances and the development of the Hybrid algorithm have been associated with higher success rates in chronic total occlusion percutaneous coronary intervention (CTO‐PCI). Nevertheless, there are still intraprocedural obstacles that result in failure or prolonged procedure time. The Excimer coronary laser (EL) has been repurposed in CTO‐PCI to overcome such obstacles. This case series illustrates the use of the EL in four technically complex scenarios including the balloon resistant lesion, the impenetrable proximal cap, device resistance in stent restenosis, and difficulty with device tracking in the subintima. © 2014 Wiley Periodicals, Inc.